TINJAUAN TENTANG PENCANTUMAN KESALAHAN BERAT DALAM PERJANJIAN KERJA BERSAMA YANG DI SAHKAN OLEH DISNAKER KABUPATEN KUTAI KARTANEGARA BERDASARKAN DENGAN PUTUSAN MAHKAMAH KONSTITUSI NOMOR : 012/PUU-I/2003 - Andi Zaenal Arman (Journal of Law ( Jurnal Ilmu Hukum ), 2020)
ABSTRACT      That in this thesis, the researcher examines the Collective Labor Agreement (CLA) in which the Collective Labor Agreement (CLA) of PT. Bukit Baiduri Energi and Union Federation of Chemicals Labor, Energy and Mining (FSPKEP) and Board of Commissioners of the Indonesian Prosperous Labor Union (SBSI) period of 2016-2018. Is still put on articles that have been appointed by Constitutional Court (CC), stated that if the labor has conducted a heavy mistake (criminal act) in the workplace as is the provision of Article 158 of Labor Law Number: 13 of 2003, then with a particular condition (evidence of the worker/laborer caught red-handed, there is a confession or supports by at least 2 witnesses) the entrepreneur can commit unilateral Employment Termination (ET), without through establishment procedure of Industrial Relations Court (IRC). Constitutional Court (CC) with Decision number: 012/PUU-I/2003 has stated that Article 158 of Labor Law, does not have binding Legal Force because it is considered as contradicted to Article 27 paragraph (1) 1945 Constitution. After the decision of the Constitutional Court (CC), the entrepreneur can no longer commit Employment Termination (ET) before general court decisions have permanent legal force (Eintracht). In this research, the researcher discusses the Collective Labor Agreement (CLA) that is not compatible with the provision which is the Collective Labor Agreement (CLA) between PT. Bukit Baiduri Energi with Union Federation of Chemicals Labor, Energy and Mining (FSPKEP) and Board of Commissioners of the Indonesian Prosperous Labor Union (SBSI)  period of 2016-2018, so that the author wants to find out the legal force and law consequences from the ratification of Collective Labor Agreement (CLA) between PT. Bukit Baiduri Energi with Union Federation of Chemicals Labor, Energy and Mining (FSPKEP) and Board of Commissioners of the Indonesian Prosperous Labor Union (SBSI) period of 2016-2018, where the results of Collective Labor Agreement (CLA) has no binding legal force because its ratification and the consequence is that the Collective Labor Agreement (CLA) is considered to have never existed because it is contradicted to the applicable Law.Keywords : Agreement, Work, Together